A Patient with Double-Negative VGKC, Peripheral Nerve Hyperexcitability, and Central Nervous System Symptoms: A Postinfectious Autoimmune Disease. (29th July 2020) - Eikeland, Birte
Abstract : Research in the last few years has indicated that most voltage-gated potassium channel- (VGKC-) complex antibodies without leucine-rich glioma-inactivated protein 1 or contactin-associated protein-like 2 antibody specificity lack pathogenic potential and are not clear markers for autoimmune inflammation. Here we report on a patient with double-negative VGKC who developed severe peripheral nerve hyperexcitability, central nervous system symptoms with agitation and insomnia, dysautonomia, and systemic symptoms with weight loss, itch, and skin lesions. The disease started acutely one month after an episode of enteroviral pericarditis and responded well to immunotherapy. The patient is presumed to have developed a postinfectious immunotherapy-responsive autoimmune disease. In the setting of anti-VGKC positivity, it seems likely that anti-VGKC contributed to the pathogenesis of the patient's symptoms of nerve hyperexcitability and that the disease was caused by an acquired autoimmune effect on the neuronal kinetics of VGKC. It is still unknown whether or not there are unidentified extracellular molecular targets within the VGKC-complex, i.e., a novel surface antigen and a pathogenic antibody that can cause affected individuals to develop a peripheral nerve hyperexcitability syndrome. This case highlights the fact that less well-characterized autoimmune central and peripheral nervous system syndromes may have infectious triggers.